Pengaruh Latihan Agility Ladder Exercise Terhadap Kemampuan Dribbling Pada Atlet Sepak Bola KU 13-15 Tahun Di Sekolah Sepak Bola (SSB) Putra Sawerigading Rante Limbong - Muhammad Indra Arif, Edy Basri, Basman (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
The purpose of this study was to determine how much to know the effect of Agility Ladder Exercise training on dribbling ability in 13-15year old soccer athletes at the Sawerigading Rante Limbong Male Soccer School (SSB). The population in this study was Population is the entire research subject". The population used was 20 people aged 13 years. The sample in this study was The sample used in this study was 20 people drawn using the purposive stratified random sampling technique. The research instrument used to collect data in this study was a test. The tool used to measure dribbling speed was a stopwatch instrument used to measure dribbling ability. Based on data analysis, the results of the study showed that there was an effect of agility leader training on the level of soccer dribbling ability in KU 13-15 SSB Puta Sawerigading Rante Limbong players. This is proven by the significance value of the count in the pretest and posttest group t-test of 0.000, which is smaller than 0.05 (Sig <0.05).